Sublethal pesticide exposure alters stress response, detoxification, and immunity gene expression in larvae of the stingless bee Frieseomelitta varia (Apidae: Meliponini) - da Silva, Jaqueline Aparecida [UNESP]; Farder-Gomes, Cliver Fernandes; Martins, Juliana Ramos; Barchuk, Angel Roberto; Malaspina, Osmar [UNESP]; Nocelli, Roberta Cornélio Ferreira (Springer Nature, 2025)
During foraging, stingless bees are at risk of pesticide contamination from treated field crops. Frieseomellita varia workers, for example, frequently visit pepper plants that are often treated with the herbicide clomazone (CLZ), the fungicide difenoconazole (DFZ), and the insecticide abamectin (ABM). These pesticides pose a threat not only to adult bees but also to larvae when the chemicals are brought back to the nest. This study aimed to evaluate the effects of sublethal concentrations of CLZ, DFZ, and ABM on the expression of stress marker proteins (HSP70AB and HSP83), detoxification enzymes (CYP9Q3, CYP6SA4, and CYTP450), and antimicrobial peptides (abaecin and defen-1) genes in F. varia larvae. First instar larvae were incubated for 48 h in ELISA plates, divided into five groups: Naive (control), acetone (acetone control), CLZ (0.014 ng a.i./µL), DFZ (0.0098 ng a.i./µL), and ABM (0.007 ng a.i./µL). After incubation, total RNA was extracted and analyzed by RT-qPCR to quantify transcript levels. While larval survival was unaffected, significant changes in gene expression patterns were observed. ABM exposure increased HSP70AB expression and decreased HSP83 expression. No changes in CYTP6SA4 expression were detected in bees exposed to any of the pesticides. DFZ suppressed CYP9Q3 expression, while ABM upregulated CYTP450 expression. Notably, the antimicrobial peptide gene abaecin was downregulated by all three compounds, whereas defen-1 expression increased in response to ABM. These findings suggest that sublethal concentrations of these pesticides can significantly alter the expression of genes associated with stress response, detoxification, and immunity in F. varia larvae. The disruption caused by herbicides and fungicides, alongside the known effects of insecticides, may impact bee physiology and colony homeostasis, with potentially unknown consequences for the survival of stingless bees in their natural environment.
Keywords: Abamectin; Antimicrobial peptide; Clomazone; Difenoconazole; HSP; P450; Stingless bees